Evaluating Arabic Language Competence Achievement in Indonesian Madrasah Tsanawiyah: A Criterion-Referenced Approach - Miftahul Ula; Ahmad Taufiq; Fakhrudin Aman; Abdul Basith (Research Journal on Teacher Professional Development, 2025)
Criterion-Referenced Assessment (PAP) is a strategic evaluation instrument in Arabic language learning, yet its implementation in madrasah still faces challenges in standard construction, achievement interpretation, and pedagogical follow-up. This study aims to explore the dynamics of PAP in evaluating Arabic language learning among seventh-grade students at MTs At-Taqwa Jatingarang. This study employs a qualitative approach with a case study design, involving teachers, students, parents, and vice principal as informants. Data were collected through semi-structured interviews, observation, and document analysis, then analyzed thematically with source and technique triangulation. The findings reveal that competence standard construction is contextual through negotiation between national curriculum and madrasah characteristics. Achievement interpretation is conducted through a qualitative matrix based on four maharah skills, enabling precise identification of competence gaps. Furthermore, PAP transforms into the heart of a continuous learning improvement cycle through remedial programs, enrichment, instructional strategy adaptation, and collaboration with parents. This study offers a new conceptual model that transforms PAP from an administrative instrument into a participatory and improvement-oriented evaluation ecosystem